TAMIL JOURNALS AND THE CIVILDISOBEDIENCE MOVEMENT (International Journal of Food and Nutritional Sciences, 2022)
The fury of the People against the British rulers reached its peak by the Non-Cooperation Movement. The People learnt how to face the Police and Military atrocities boldly. Courting arrest for the national cause became an act of Patriotism. The Country Was Once again prepared for Civil Disobedience and great enthusiasm was exhibited admirably when the movement actually started in 1930.